Analisis Faktor-Faktor Fraud Pentagon Teori Pada Fraudelent Financial Report - Indah Yunita Sari; Fatchur Rohman (Jurnal Dinamika Ekonomi & Bisnis, 2022)
Fraudulent financial report is caused by the company's efforts to show the company's financial condition as well as possible to potential investors with the aim to make them have the desire to invest and cooperate with the company. This research aims to analyze the fraud pentagon factors that influence the emergence of fraudulent financial reports in manufacturing companies in the consumer product industry listed on the Indonesia Stock Exchange (IDX) during 2017 – 2020. The fraud pentagon variables include external pressure, ineffective monitoring, change in auditor, change of directors, and frequent number of CEO pictures. The population in this research were manufacturing companies in the consumer product industry that submit complete and good financial reports on the IDX or on the company's website. The sampling technique used was purposive sampling, and the data were analyzed using multiple linear regression analysis assisted by SPSS version 20 software. In this research, it was found that the external pressure variable positively affects the fraudulent financial report, while the ineffective monitoring, change in auditor, change of director, and frequent number of CEO pictures variables did not have an effect on the fraudulent financial report.